此人端为救时来—— 论沈家本纪行诗中的忧患意识与家国情怀: This person comes to save the time era—— On the ideological consciousness in Shen Jia Ben's travelogue poems - Lu Na; Khor , Teik Huat (ERUDITE: Journal of Chinese Studies and Education, 2024)
沈家本（1840-1913）是近代中国法律文化的奠基人和诗人。他一生创作了六百多首诗，其中二百多首反映了他在游历迁徙过程中的心路历程。沈家本的诗作不仅具有文学艺术的魅力，更具有思想性，深刻反映了那个时代的历史背景和社会风貌。他以诗歌为媒介，表达了对国家未来的期许和呼吁，激发了民众对社会进步和民生改善的渴望。本文旨在通过评述沈家本各时期的纪行诗，通过诗作中青年时期的“忧国情”、中年时期的“报国志”、老年时期的“思国运”三个维度，展现这位立志修律救国的清末士大夫身上浓厚的忧患意识和家国情怀。Shen Jiaben, a prominent figure in modern Chinese legal culture and a great poet, dedicated his life to the creation of over six hundred poems, with more than two hundred reflecting his emotional journey during his travels and migrations. Shen Jiaben's poetic works possess not only literary charm but also scholarly significance, providing profound insights into the historical backdrop and social landscape of his time. Through the medium of poetry, he expressed his aspirations for the future of the nation and called upon the people, inspiring a desire for social progress and improved livelihoods. This article aims to explore Shen Jiaben's historical journey through his travelogue poems, highlighting the dimensions of his youthful concerns for the country, his middle-aged devotion to the nation, and his contemplation of the nation's fate in his later years. These poems vividly depict the unwavering commitment, selfless dedication, and resolute determination of this scholar-official of the late Qing dynasty, who held a strong sense of concern and patriotism.Keywords：Shen jiaben, travelogue poem, ideological awareness